A student-centred approach: Assessing the changes in prospective science teachers' conceptual understanding by concept mapping in a general chemistry laboratory - Kaya, Osman Nafiz (Springer, 2008)
Although researchers in higher education propose alternatives to traditional approaches to assessment, traditional methods are commonly used in college or university science courses. The purpose of this study was to explore the feasibility and validity of Prospective Science Teachers' (PSTs) concept maps as authentic assessment tools in a student-centred approach to describe the changes in the conceptual understanding of the PSTs in general chemistry laboratory investigations. After the PSTs (n=47) decided on important issues, such as who would assess their concept maps and what scoring strategy and criteria would be used, they practiced assessing their own and peers' concept maps during the first five laboratory investigations. They subsequently constructed and assessed pre- and post-laboratory concept maps in a student-centred approach consisting of self, peer, and instructor assessments for the five remaining laboratory investigations. The results of the study showed using pre- and post-laboratory concept maps as authentic assessment tools in a student-centred approach was valid and reliable for describing the conceptual understanding of the PSTs in a university general chemistry laboratory course. The results of individual interviews indicated most PSTs had positive views of their assessment practices in the laboratory course. This study also provides pedagogical implications for the training of science teachers.
Keywords: authentic assessment; science teacher education; science laboratory; concept mapping